STUDY ASBABUN NUZUL DAN RELEVANSINYA DALAM MEMAHAMI KONTEKS AYAT AL-QUR'AN - Siti Salma Saludi; Muhammad Tajuddin (STKIP Subang, 2026)
This study aims to explore the role of asbabun nuzul (the contexts of revelation) in understanding the context of Quranic verses and its relevance to modern life. The method employed is a qualitative approach utilizing library research, where data were gathered through documentation techniques from various primary and secondary literatures related to Quranic studies. Data analysis was conducted using content analysis to present the findings comprehensively. The findings indicate that understanding asbabun nuzul provides deep insights into the ethical, social, and legal values contained within the Quran. In the ethical context, values such as honesty and integrity can be applied to digital communication. Socially, this understanding promotes justice, equality, and harmony in a multicultural society. In the legal realm, the background of a verse's revelation is crucial for formulating policies that are responsive to contemporary challenges. The conclusion of this study confirms that applying Quranic values through the lens of asbabun nuzul renders them relevant and highly solution-oriented for contemporary issues.